DEVELOPMENT OF CPA-BASED INTERACTIVE MULTIMEDIA TO IMPROVE ELEMENTARY SCHOOL STUDENTS' MATHEMATICAL CREATIVE THINKING SKILLS - Yuliyanto, Aan; Bayuni, Tia Citra; Zahrah, Dania Isnaeni; Rabbani, Nida Ul Husna; Yani Fitriyani; Azmi Endah Permatasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research was motivated by the low mathematical creative thinking skills of elementary school students on the material of flat shapes. The study aimed to develop interactive multimedia based on the Concrete-Pictorial-Abstract (CPA) approach. The research method was Research and Development (R&D) using the 4D model, including Define, Design, Develop, and Disseminate. The product developed was an interactive multimedia that combines text, images, animation, audio, and interactive exercises based on the CPA stages. The research subjects were 30 control class students and 29 experimental class students of an elementary school in North Cikarang, Bekasi. The instruments included observation, interviews, expert validation questionnaires, user response questionnaires, and mathematical KBK tests. Data were analyzed quantitatively and qualitatively. The results showed that interactive multimedia obtained a very valid category based on expert assessments, with a score breakdown of material experts giving an assessment of 92.5%, media experts 92.5%, and language experts 85%. Overall, the average percentage of product feasibility reached 90%, which places the product in the very valid and suitable category for use. Regarding practicality, the results of the student questionnaire obtained an average of 93% (very practical). The effectiveness results with N-Gain showed a KBK score of 0.69 (69%) in the moderate category. This indicates that students considered interactive multimedia interesting, easy to understand, and very helpful in understanding the material from the concrete to the abstract stage. The product was declared feasible and effective in facilitating fluency, flexibility, originality, and detail of mathematical creative thinking. Thus, interactive multimedia based on the CPA approach has the potential to be an effective and practical medium to improve the quality of mathematics learning in elementary schools.